2014
DOI: 10.1186/1471-2415-14-61
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of surgical management for rhegmatogenous retinal detachment in Behçet’s disease

Abstract: BackgroundThe purpose of the current study is to evaluate the surgical outcome for rhegmatogenous retinal detachment (RD) associated with Behçet’s disease (BD).MethodsThe current retrospective study included all patients operated for rhegmatogenous RD associated with BD in our institution from June 2007 to June 2012. Surgical repair was done either by scleral buckling (SB) or pars plana vitrectomy (PPV) according to the topography and clinical criteria of the detachment.ResultsThe current study included 7 eyes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
3
4
0
Order By: Relevance
“…[27][28][29][30][31][32] Prior intravitreal injections might form a predisposing factor for RRD development. This was already noted in previous reports 33,34 which hypothesized that intravitreal injection might induce PVD and thereby increase a risk of retinal tears. In our study, with the application of multivariate analysis, we cannot confirm this association.…”
Section: Discussionsupporting
confidence: 70%
“…[27][28][29][30][31][32] Prior intravitreal injections might form a predisposing factor for RRD development. This was already noted in previous reports 33,34 which hypothesized that intravitreal injection might induce PVD and thereby increase a risk of retinal tears. In our study, with the application of multivariate analysis, we cannot confirm this association.…”
Section: Discussionsupporting
confidence: 70%
“…Our findings are in concordance with a few reported cases [ 6 , 8 ]. Mesquida et al ., in a retrospective review, reported three eyes with retinal detachments managed with PPV in patients with vitreoretinal complications of Behçet’s-associated uveitis.…”
Section: Discussionsupporting
confidence: 94%
“…Posterior segment sequelae of BD requiring surgical management include persistent vitreous opacities, vitreous hemorrhage, epiretinal membrane, macular hole and rarely retinal detachment [ 6 , 7 ]. Data regarding the surgical management of retinal detachment in eyes with BD is sparse, and even more limited for combined rhegmatogenous retinal detachment and tractional retinal detachment (RRD/TRD) involving the macula [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…One-stage surgery could simultaneously resolve cataract and posterior segment involvement, thereby shortening patient discomfort, reducing costs and accelerating visual recovery. Our results obtained using combined phacoemulsification, IOL implantation and MIVS in a single surgery confirm the efficiency of this technique, which has been described in previous reports [ 13 16 ]. Moreover, MIVS improves operative efficiency and is a relatively non-invasive surgery with an acceptable complication rate and mild postoperative inflammatory reactions.…”
Section: Discussionsupporting
confidence: 90%